Developing architecture of system management in the English NHS: evidence from a qualitative study of three Integrated Care Systems. Issue 2 (8th February 2023) - Sanderson, Marie; Allen, Pauline; Osipovic, Dorota; Petsoulas, Christina; Boiko, Olga; Lorne, Colin
Abstract : Objective: Integrated Care Systems (ICSs) mark a change in the English National Health Service to more collaborative interorganisational working. We explored how effective the ICS form of collaboration is in achieving its goals by investigating how ICSs were developing, how system partners were balancing organisational and system responsibilities, how partners could be held to account and how local priorities were being reconciled with ICS priorities. Design: We carried out detailed case studies in three ICSs, each consisting of a system and its partners, using interviews, documentary analysis and meeting observations. Setting/participants: We conducted 64 in-depth, semistructured interviews with director-level representatives of ICS partners and observed eight meetings (three in case study 1, three in case study 2 and two in case study 3). Results: Collaborative working was welcomed by system members. The agreement of local governance arrangements was ongoing and challenging. System members found it difficult to balance system and individual responsibilities, with concerns that system priorities could run counter to organisational interests. Conflicts of interest were seen as inherent, but the benefits of collaborative decision-making were perceived to outweigh risks. There were multiple examples of work being carried out across systems and 'places' to share resources, change resource allocation and improve partnership working. Some interviewees reported reticence addressing difficult issues collaboratively, and that organisations' statutory accountabilities were allowing a 'retreat' from the confrontation of difficult issues facing systems, such as agreeing action to achieve financial sustainability. Conclusions: There remain significant challenges regarding agreeing governance, accountability and decision-making arrangements which are particularly important due to the recent Health and Care Act 2022 which gave ICSs allocative functions for the majority of health resources for local populations. An arbiter who is independent of the ICS may be required to resolve disputes, along with increased support for shaping governance arrangements.